2008
DOI: 10.1007/s10310-008-0063-y
|View full text |Cite
|
Sign up to set email alerts
|

Fine root biomass and morphology of Pinus densiflora under competitive stress by Chamaecyparis obtusa

Abstract: The fine root (diameter B2.0 mm) biomass and morphology of Japanese red pines (Pinus densiflora) grown under different aboveground conditions (i.e., high and low competitive environments) were examined in a pinecypress mixed forest. All P. densiflora subject trees were about 40 years old, and the aboveground condition (i.e., size) of red pines appeared to be influenced by the surrounding Japanese cypress (Chamaecyparis obtusa). Smaller P. densiflora exhibited lower fine root biomasses, shorter root lengths, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…Recent debates have focused on whether growth or allocation plasticity is more dominant in response to abiotic stress (Chmura et al, 2017;Curt et al, 2005;Fujii & Kasuya, 2008;Kramer-Walter & Laughlin, 2017;Valladares et al, 2005). Previous studies showed that allocation traits vary little under biotic or abiotic stress (Curt et al, 2005;Kaelke, Kruger, & Reich, 2001;Reich et al, 1998).…”
Section: Growth Plasticity Versus Allocation Plasticitymentioning
confidence: 99%
“…Recent debates have focused on whether growth or allocation plasticity is more dominant in response to abiotic stress (Chmura et al, 2017;Curt et al, 2005;Fujii & Kasuya, 2008;Kramer-Walter & Laughlin, 2017;Valladares et al, 2005). Previous studies showed that allocation traits vary little under biotic or abiotic stress (Curt et al, 2005;Kaelke, Kruger, & Reich, 2001;Reich et al, 1998).…”
Section: Growth Plasticity Versus Allocation Plasticitymentioning
confidence: 99%
“…Trees that suffer from strong interspecific or intraspecific competition tend to have higher specific root length (SRL), and bigger specific root surface area or number of root tips per root length unit. Fujii and Kasuya (2008) found nearly double the value of specific fine root length of Pinus densiflora grown in an intensely competitive environment of dense Chamaecyparis obtusa, compared to environment with reduced competition. According to Bolte et al 2013, beech is able to raise significantly its SRL, while growing with spruce competitors.…”
Section: Introductionmentioning
confidence: 81%
“…In the case of L. glaber, the higher SRL and SRA values suggest higher nutrient absorption efficiency for this species when coexisting with P. massoniana in mixed forests. Given that L. glaber had a lower fine root biomass than P. massoniana in mixed species stands, it would seem that L. glaber fine roots may alter their individual morphologies, to compensate for their lower overall biomass (Fujii and Kasuya 2008). The lower SRL and SRA values observed for P. massoniana are probably attributable to the fact that coniferous species are to some extent dependent on ectomycorrhizal associations (Bauhus and Messier 1999) to facilitate assisting nutrient uptake.…”
Section: Fine Root Morphological Plasticity and Belowground Interactionsmentioning
confidence: 94%
“…(Jacob et al 2013). Moreover, fine root morphological traits may also differ in mixed species forests relative to monocultures because trees that experience intense competition tend to show increased SRL and SRA values (Fitter 1991;Fujii and Kasuya 2008). For example, coniferous species in mixed stands showed much higher fine root length per unit stem basal area compared to monospecific neighbourhoods ).…”
mentioning
confidence: 95%
See 1 more Smart Citation